Effect of Sugarcane Polyphenol Extract on α-Amylase Inhibition and Mechanism Exploration - Yumei Wang; Jiulong An; Shenghong Yao; Chengfeng Zhang; Yanv Zhou; Lu Li; He Li (Foods)
Although α-amylase is crucial for postprandial glucose control, existing inhibitors present various side effects, necessitating the exploration of natural alternatives. The ability of sugarcane polyphenol (SP) to inhibit α-amylase remains unclear. This study assessed the inhibitory activity of SP via in vitro assays, circular dichroism (CD), fluorescence quenching, and stability analysis, while the mechanism of action was elucidated using molecular docking and molecular dynamics (MD). The results showed that the IC50 of the SP was 0.841 ± 0.029 mg/mL, with proanthocyanidin-B1 (PC-B1) presenting the most potent effect (IC50 = 0.504 ± 0.019 mg/mL). CD and barycentric mean (BCM) analysis indicated that the complexes might limit substrate binding. The mechanistic assessment showed that the polyphenols bonded to the active enzyme pockets to form stable complexes with reduced key residue fluctuations. In conclusion, SP, especially PC-B1, effectively inhibited α-amylase activity via structural regulation and molecular interactions, providing a theoretical basis for developing natural hypoglycemic agents.